Los inventarios de repuestos de las unidades de recolección de desechos sólidos, y su impacto en los estados financieros del consorcio puerto limpio de la ciudad de Guayaquil - Méndez Tacuri, Bertila Faviola (2017)
The following article deals with the inventories of solid waste collection units spare parts and their impact on the financial statements of the Consorcio Puerto Limpio in the city of Guayaquil; The inventories are part of the important assets within the company, since they contribute to the development of the turn of the business, the lack of a good management and an effective control of the inventories of spare parts causes several problems. For the development of the topic we carry out information surveys, analysis of the Company's Financial Statements to examine the Inventory account and how it affects, we also proceed to validate the Financial Statements through the management and liquidity ratios…….